Patterns, Programming and Everything - Breitman, Karin K.; Horspool, R. Nigel (Springer London : Imprint: Springer, 2012)
With 11 invited submissions from leading researchers and teams of researchers sharing one common characteristic - all have worked with Dr. Judith Bishop during her long and continuing career as a leader in computer science education and research - this book reflects on Dr Bishop's outstanding contribution to computer science. Having worked at three different universities she now holds a leadership position in the research division of a major software company. The topics covered reflect some of the transitions in her career. The dominant theme is programming languages, with chapters on object oriented programming, real-time programming, component programming and design patterns. Another major and related topic is compilers, with contributions on dataflow analysis, tree rewriting and keyword recognition. Finally, there are some additional chapters on other varied but highly interesting topics including smart homes, mobile systems and teaching computer science.